PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada PT. Taspen (Persero) Cabang Manado) - Peoni, Herianus (Sam Ratulangi University, 2014)
This research aim to to know influence of Environmental and Individual Characteristicof Activity to Performance Employees. Data Research in obtaining to through interview withcompany side and also spreading of kuesioner to 32 employees, and use approach of SimpleCorrelation Analysis and Doubled Linear Regression. Result of research show Environmentaland individual Characteristic of Job by together have an effect on to Performance Employees.But Environment Work by parsial more big having an effect on to Performance Employeescompared to Individual Characteristic.Result of research with correlation express there are relation which is signifikan, thatX1 (Individual Characteristic) and X2 (Environmental work) to Y (Performance Employees)by using test of t got that value of thitung = 4,221 + 0,592 from value of ttabel = 1.611 withstorey;level of signifikan smaller than value = 0,05. Value of R equal to 0,743 can beinterpreted that relation between variable of X (Environmental and Individual Characteristicof Activity) to variable of Y (Performance Employees) is strength, because progressivelycome near number 1. Assess R Square equal to 0,552 or 55,2% explaining the level ofinfluence of variable of X (Environmental and Individual Characteristic of Activity) tovariable of Y (Performance Employees). Assess R Square above can be interpreted that levelof influence of variable of X to Y is equal to 55,2%, while the rest 44,8% influenced by othervariable outside accurate variable in this research.Conclusion of this research is there are influence between Environmental andIndividual Characteristic of Activity to Performance Employees At PT. Taspen Conclusion ofthis research is there are influence between Environmental and Individual Characteristic ofActivity to Performance Employees At PT. Taspen (Persero) Office Of Branch of Manado.Keywords : Individual Characteristic, Environment Work, Performance Employees.